Theory and Social Research Methods: A Study of Public Policy in Flood Disasters’ Mitigation in Illushi Community in Edo State - Aigberadion, Iboaya, Benson; Amenaghawon, Ehrim Joy (Kashere Journal of Politics and International Relations, 2025)
Theory is central to the research process. It is the lens for viewing problems; and the way to fashion out solutions. Theory determines the research hypothesis, research design, and generalization. A theory enhances the scientific content of research and the search for solution to social problem. A theory is a mental map of reality. Applying theories to social research began with the behavioural revolution which emphasized empirical studies such as Public Policy in Flood Disasters’ Mitigation in Illushi Community of Edo State. In 2012 and 2018, disastrous floods were witnessed in Illushi. The qualitative research method was used. The main objectives of this study are to find out: the role of theory on social research methods featuring Public Policy and Mitigation of Flood Disasters in Illushi; the impact of theory on formulation of hypothesis; and Enhancement of capacity to predict outcomes and make generalization. The Theoretical Framework is anchored on System Theory; and Structural-Functional Theory. Findings reveal that government aid to mitigate the hardships on flood victims in the study area was insufficient; theory enhances the scientific content of research; theory promotes the formulation of hypothesis; and theory promotes the prediction and generalization of the research. This study makes the following recommendations: There should be an overhaul of the Public Policy on Mitigation of Flood Disasters; and Theory and scientific empirical data should be fully incorporated into Social Research Methods.